Complementary results on sex-, age-, and cause-specific mortality in EU countries obtained by SYR symbolic data analysis software - Lotrič Dolinar, Aleša (Metodološki zvezki, 2022)
Different mortality patterns across countries require different health and demographicpolicies. Positioning of the countries according to their characteristic mortality pattern canhelp allocate scarce resources appropriately. We use symbolic data analysis within SYRsoftware to analyse 28 European Union countries' sex-, age-, and cause-specific mortalityin 2015. There are two main advantages for using symbolic analysis:(i) it permits moretransparent and informative data descriptions along with contextual relations, and(ii) advanced methods adapted for complex data representations can be employed to analyse suchdata, taking contextual relations into account. Clustering results based on symbolic dataanalysis show that groups of countries are strongly related to the geographical positionof countries, with a clear east-west cut on the first-level partition and with an even moregeographically consistent lower-level partition compared to the classical clustering result.Relations between the obtained clusters of countries and their external social and healthindicators are well pronounced. We also identify the mortality rates as symbolic variablesthat discriminate the most between individual countries as well as between the resultingclusters. Knowledge of a country's mortality pattern and its position among comparablecountries is valuable information for health and demographic policymakers and can beexploited to exchange good practices.
Keywords: analiza podatkov; demografska statistika; Evropska unija; metodologija; mortaliteta; smrtnost; zdravstvo